Analisis DSSC menggunakan mulberry powder dan buah naga sebagai fotosensitizer - Nurlaila Rajabiah; Dwi Irawan (Universitas Muhammadiyah Metro, 2022)
Fabrication prototype of DSSC (Dye-Sensitized Solar Cell) using mulberry powder from mulberry leaf extract (Morus Alba L.) and dragon fruit (Hylocereus Polyrhizus) as photosensitizers has been carried out. The test was carried out by testing the I-V characteristics at a light distance of 10, 20 and 30 cm from the material sample. The test results show that the chlorophyll of mulberry and dragon fruit is capable of producing an electric current which is a characteristic of the resistance of organic materials. In DSSC with mulberry powder dye, the greatest power was found at a halogen lamp distance of 10 cm with a power of 257.77 mW. Whereas in DSSC with red dragon fruit flesh dye, the greatest power was obtained at 162.35 mW with the halogen lamp distance from the DSSC device being 10 cm. DSSC testing using mulberry powder and dragon fruit showed that the power produced on mulberry powder leaves was higher than dragon fruit. The results of the I-V characteristic test on the DSSC device show a linear graph.